Increase in backbone mobility of the VTS1p-SAM domain on binding to SRE-RNA - Ravindranathan, Sapna; Oberstrass, Florian C.; Allain, Frederic H. T. (Journal of Molecular Biology, 2010)
The sterile alpha motif (SAM) domain of VTS1p, a posttranscriptional gene regulator, belongs to a family of SAM domains conserved from yeast to humans. Even though SAM domains were originally classified as protein-protein interaction domains, recently, it was shown that the yeast VTS1p-SAM and the SAM domain of its Drosophila homolog Smaug can specifically recognize RNA hairpins termed Smaug recognition element (SRE). Structural studies of the SRE-RNA complex of VTS1p-SAM revealed that the SAM domain primarily recognizes the shape of the RNA fold induced by the Watson-Crick base-pairing in the RNA pentaloop. Only the central G nucleotide is specifically recognized. The VTS1p-SAM domain recognizes SRE-RNAs with a CNGGN pentaloop where N is any nucleotide. The C1-G4 base pair in the wild type can be replaced by any pair of nucleotides that can form base pairs even though the binding affinity is greatest with a pyrimidine in position 1 and a purine in position 4. The interaction thus combines elements of sequence-specific and non-sequence-specific recognitions. The lack of structural rearrangements in either partner following binding is rather intriguing, suggesting that molecular dynamics may play an important role in imparting relaxed specificity with respect to the exact combination of nucleotides in the loop, except for the central nucleotide. In this work, we extend our previous studies of SRE-RNA interaction with VTS1p, by comparing the dynamics of the VTS1p-SAM domain both in its free form and when bound to SRE-RNA. The 1 5 N relaxation studies of backbone dynamics suggest the presence of a dynamic interaction interface, with residues associated with specific G3 recognition becoming more rigid on RNA binding while other regions attain increased flexibility. The results parallel the observations from our studies of dynamics changes in SRE-RNA upon binding to VTS1p-SAM and shows that molecular dynamics could play a crucial role in modulating binding affinity and possibly contribute to the free energy of the interaction through an entropy-driven mechanism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: (15)N relaxation; NMR; protein-RNA interaction; SRE-RNA; VTS1p-SAM domain